Study of fatigue in AISI 4340 steel with different microstructural conditions, submitted to a surface treatment of shot peening - Molento de Moraes, Carlos Eduardo; Baptista, Carlos Antonio Reis Pereira; dos Santos Torres, Marcelo Augusto [UNESP]; Fonseca, Maria Cindra; Abdalla, Antonio Jorge (Trans Tech Publications, 2016)
The AISI 4340 steel has been largely employed for structural purposes, which requires resistance levels with yield strength above 1400 MPa and it attains high levels of resistance in dual phase, bainitic or martensitic microstructural conditions. The samples of AISI 4340 steel with different microstructural conditions (martensitic, bainitic and ferritic/perlitic) have been submitted to fatigue tests on push-pull mode. Subsequently, the new specimens underwent a shot peening surface treatment and new fatigue tests. The results have been discussed in comparison to the three microstructural conditions studied and they were related to a microstructural characterization. The results have showed that a shot peening treatment is not always beneficial to fatigue life, since there is a relationship between the compressive stresses developed on the surface and its roughness formed due to the deformations. Under the three microstructural above studied it was noticed a strong fatigue life reduction in the martensitic condition because such microstructure is considered less ductile.
Keywords: AISI 4340 steel; Fatigue; Microstructural characterization; Shot peening